ANALISA PEMBAGI FREKUENSI UNTUK PHASE LOCKED LOOP BERBASIS IC TC9122 - Ashari, M. Ibrahim; Setiawan, Rachmadi (DINAMIKA DOTCOM, 2018)
In FM radio receivers many frequency instabilities are found in the form of interference from other transmitter radio frequencies. This requires a frequency locking system that can lock the frequency of the relationship between the reference frequency and the frequency wave generated by VCO. The locking system is the Phase Locked Loop system. The Phase Locked loop system requires a divider frequency circuit that uses IC TC9122, input the IC frequency divider will experience a division process that is controlled by a DIP Switch that has been calculated based on the desired frequency to be locked. With this background, it is necessary to create Frequency Dividers for Phase Locked Loops Based on IC TC9122